The role of digital supply chain practices in enhancing firm performance: insights from the manufacturing sector of Bangladesh - Khan, Tahsina; Emon, Md Mehedi Hasan (Brazilian Journal of Operations & Production Management, 2025)
Purpose: This study examines the impact of digital supply chain practices (DSCP) on firm performance (FP) in the context of Bangladesh’s manufacturing sector, with a focus on supply chain responsiveness (SCR) and customer development (CD) as mediating factors. Design/methodology/approach: A quantitative research design was employed, utilizing partial least squares structural equation modeling (PLS-SEM) to analyze survey data collected from 438 participants representing manufacturing firms in Bangladesh. The model evaluates the direct effects of DSCP on FP, as well as the mediating roles of SCR and CD. Findings: Results indicate that DSCP positively and significantly impacts FP, with SCR and CD serving as effective mediators in this relationship. The study demonstrates that digital integration in supply chains enhances responsiveness and customer engagement, ultimately leading to improved organizational performance. Through increased operational efficiency, streamlined logistics, and improved decision-making, the results show that Digital Supply Chain Practices (DSCP) are essential for boosting company performance. By empowering businesses to quickly adjust to market needs, minimize interruptions, and maximize resource usage, DSCP improves supply chain responsiveness and, in the end, increases agility and competitive advantage. Additionally, by enhancing engagement, trust, and service quality, DSCP improves customer development, which supports long-term business success and sustainability in Bangladesh’s manufacturing industry. Research limitations/implications: The study is limited by its focus on the manufacturing sector in Bangladesh, which may affect the generalizability of findings to other industries or regions. Future studies should examine additional variables, such as organizational culture and market conditions, that may influence DSCP’s effectiveness. Practical implications: The findings provide actionable insights for managers seeking to enhance performance through digital supply chain integration. Investing in digital tools can improve responsiveness and customer satisfaction, driving organizational success in competitive markets. Social implications: This study underscores the potential of digital transformation to improve supply chain efficiency, fostering economic growth and sustainability in emerging economies like Bangladesh. Originality/value: This research contributes to the limited literature on digital supply chains in developing economies, offering empirical evidence of their role in improving firm performance.